Media image of the country in international broadcasting: concept components and formation strategies - Piatkevich, Viktoryia M. (Journal of the Belarusian State University. Journalism, 2019)
This paper presents the concept «media image» from the perspective of two aspects: firstly as a complex polysystemic psychological formation and secondly as a summary view to the country, created by the media through reflection in journalistic materials (concept «media image of the state»). Today creating a positive image of the state mass media take into account the following: the historical past, traditions and customs, economic, sport, educational, cultural and other achievements, lifestyle, ecology. Despite the fact the level of representation of these aspects can fluctuate, the most important is target filling of every informational cell in the media consciousness of people. The principles and tools of reality constructing have been regularly changed in accordance with changes at the global and local levels, therefore the theory of reality constructing under the direct influence of the media cannot be formulated comprehensive. The realization of these opportunities in the field of mass media depends on the choice of the most effective communicative strategies, determined as a complex of tools and ways of country promotion in the media space. There fore the formation of the external media image of the country should be implemented through the integrated implementation of four key strategies: modeling strategy, image strategy, content strategy and communication strategy.